Talking dirty on Sex and the city : romance, intimacy, friendship - Oria, Beatriz, 1981- (Rowman and Littlefield, 2014)
Sex and the City (1998-2004) was one of the most popular programs on HBO, spawned two successful feature films in 2008 and 2010, and continues to do well in syndication. This book explores how Sex and the City represents the conventions of romantic comedy in order to create a familiar fictional world of intimacy, gender identity, and interpersonal relationships. Rather than tackle debates about whether the show was revolutionary or conservative in its representation of gender, class, race, and female sexuality (which has already been covered by other books), the author discusses the show's com.